2008
DOI: 10.1590/s1980-57642009dn20300007
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial cognitive tests for the evaluation of patients with Parkinson's disease

Abstract: Parkinson's disease (PD) is a neurological disorder characterized by motor disturbances, neuropsychological symptoms and cognitive changes, including cases of dementia. The most frequently described cognitive changes in these patients involve executive and visuospatial functions, which are very important for the execution of daily life activities.ObjectiveTo compare different tests used to examine visuospatial functions in patients with PD.MethodsThirty-five patients (21 women) with PD symptoms (medicated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…[44][45][46] Oktem et al found significant correlation between retinal thickness and mild cognition in AD patients as compared with control group. 47 However, our results have shown that visuospatial memory is independent of retinal injury induced by laser photocoagulation.…”
Section: Discussionmentioning
confidence: 49%
“…[44][45][46] Oktem et al found significant correlation between retinal thickness and mild cognition in AD patients as compared with control group. 47 However, our results have shown that visuospatial memory is independent of retinal injury induced by laser photocoagulation.…”
Section: Discussionmentioning
confidence: 49%
“…Esse aspecto demonstra a importância de se considerar o nível de escolaridade nas normas de todos os instrumentos, sejam eles verbais ou não verbais (Javadi et al, 2015). Além de que elas também auxiliam na verificação de prejuízos visuoespaciais e na detecção de dificuldades em outros componentes cognitivos que possam estar comprometidos, como atenção, funções executivas e habilidades motoras (Pena et al, 2008).…”
Section: Resultsunclassified
“…On the other hand, episodic memory is less affected and patients with MCI usually have more difficulty in free recall than cued recall in memory tests (such as a list of words or pictures). A previous study exploring visuospatial dysfunctions in PD patients showed that 62.2% of 35 patients could not copy the pentagon drawing 26 . Moreover, Machado et al suggested that language and visual organization tend to follow motor skills and general cognitive performance in patients with DLB 27 .…”
Section: Clinical Features In Pdd and Dlbmentioning
confidence: 95%